1965
DOI: 10.1590/s0006-87051965000100017
|View full text |Cite
|
Sign up to set email alerts
|

Hibridações entre Coffea arabica e C. kapakata. análise citológica de um híbrido triplóide

Abstract: Os cruzamentos realizados entre Coffea arabica e C. kapakata revelaram que há possibilidade de hibridação entre estas duas espécies e que o pegamento é bem mais elevado quando C. arabica é usada como planta feminina. Os resultados das hibridações realizadas, acrescidos aos já existentes sôbre a relação de compatibilidade de C. kapakata com outras espécies, vêm reforçar a sua inclusão dentro do gênero Coffea. As observações feitas na meiose de um híbrido triplóide entre C. arabica e C. kapakata demonstraram a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Many of the irregularities reported in the process of meiotic division in this study were also found in other studies with coffee hybrids, such as C. racemosa and C. arabica (Medina 1963), C. arabica and C. kapakata (Mônaco and Medina 1965), C. dewevrei and C. eugenioides, C. liberica and C. eugenioides (Reddy and Narayan 1981), and C. arabica and C. canephora (4x) (Owuor 1985;Boaventura and Cruz 1987). Furthermore, some meiotic abnormalities observed in the F 2 population could also reflect the doubling of the single diploid C. canephora genome or incompatibility caused by genomic divergence between their parents.…”
Section: Unisupporting
confidence: 87%
See 1 more Smart Citation
“…Many of the irregularities reported in the process of meiotic division in this study were also found in other studies with coffee hybrids, such as C. racemosa and C. arabica (Medina 1963), C. arabica and C. kapakata (Mônaco and Medina 1965), C. dewevrei and C. eugenioides, C. liberica and C. eugenioides (Reddy and Narayan 1981), and C. arabica and C. canephora (4x) (Owuor 1985;Boaventura and Cruz 1987). Furthermore, some meiotic abnormalities observed in the F 2 population could also reflect the doubling of the single diploid C. canephora genome or incompatibility caused by genomic divergence between their parents.…”
Section: Unisupporting
confidence: 87%
“…Hybrids between the species C. arabica and C. canephora have been obtained on different occasions, and they are called "Arabusta" (Mendes 1950). Because of its importance, meiotic behavior had already been studied to some F 1 hybrids and also to parental plants in order to explore the genetic resources of these hybrids (Mendes 1950;Medina 1952;Medina 1963;Mônaco and Medina 1965;Medina and Rijo 1969;Reddy and Narayan 1981;Owuor 1985;Boaventura and Cruz 1987;Boaventura 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Its meiotic behaviour is diploid-like (Medina 1950;Mendes 1950;Mendes et al 1954;Grassias and Kammacher 1975). Presence of two genomes in ARA has been suggested from the meiotic behaviour of haploids (Berthaud 1976;Carvalho 1952;Vishveshwara 1960) and F1 hybrids (at triploid, tetraploid and hexaploid levels) between this species and other CoVea species (Berthaud 1978;Chinnappa 1968;Kammacher and Capot 1972;Louarn 1976;Medina 1963;Monaco and Medina 1965). The presence of a C. eugenioideslike genome as female parent of ARA has been emphasized from chloroplast DNA sequence comparisons (Berthou et al 1980;Cros et al 1998).…”
Section: Introductionmentioning
confidence: 99%